'We need to share our stories': the lives of Pakistanis with intellectual disability and their guardians. Issue 5 (13th March 2020) - Patka, M.; Wallin‐Ruschman, J.; Al Rahma, B. A.; Zar, A.; bin Nauman, H.; Sharif, J. M.; Ikram, S.; Ul Hasan, T.; Naeem, A.; Sharif, G. M.; Mehboob, N.; Azim, T.; et al.
Abstract: Introduction: The experiences of Pakistanis with intellectual disabilities (IDs) and their family members have been underexplored empirically. Method: The present study sought to address this gap by understanding the lives of five Special Olympics Pakistan athletes and their guardians through PhotoVoice. Findings: Through thematic analysis, we present the primary theme concerning Pakistan's cultural context that provides an empirical exploration of cultural beliefs about intellectual disability, cultural expectations and support received by people with intellectual disabilities and their guardians. Discussion: We discuss implications for research and practice.